(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2014)
Social justice is inserted in a national legal order, where it is explained at the subparagraph at article number 3 at the Federal Constitution of 1988 as a fundamental objective at the Federative Republic of Brazil, as well as per the caput article number 170 from the same legal certificate – it is the base where it lies social assistance as an attendance instrument for the distraught. The State has such a prerogative and simultaneously duty to act upon any of such Powers – Legislative, Executive or Judiciary – upon risk scenarios or threat towards life and human dignity in order to make sure what is minimally necessary to existence. Having considered poverty and exclusion as constitutive highlighting guidelines to social procedures in Latin America, such article aims in analyzing the guidelines surrounding social assistance systems of some countries compounding it.